If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 66 = 2x + 1 Reorder the terms: 66 + 7x = 2x + 1 Reorder the terms: 66 + 7x = 1 + 2x Solving 66 + 7x = 1 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 66 + 7x + -2x = 1 + 2x + -2x Combine like terms: 7x + -2x = 5x 66 + 5x = 1 + 2x + -2x Combine like terms: 2x + -2x = 0 66 + 5x = 1 + 0 66 + 5x = 1 Add '-66' to each side of the equation. 66 + -66 + 5x = 1 + -66 Combine like terms: 66 + -66 = 0 0 + 5x = 1 + -66 5x = 1 + -66 Combine like terms: 1 + -66 = -65 5x = -65 Divide each side by '5'. x = -13 Simplifying x = -13
| -9•(-4/3) | | 18v=-13 | | 5x+9-3x=-2 | | 1-5x=-1x-8 | | 8(2x-4)-9(X+2)=2-5x | | 225=180-y | | -40+(-10n)=-110 | | 37x+4-19x=22 | | V/5=6.25 | | (5x^2-7x-9)+(3x^2-5x+8)-(x^2-5x-3)= | | 4(u-5)=7u-32 | | 2x-7+3x=10 | | 43.75=7u | | -4(1/4)^-2 | | -10=-4+2u | | 60-40y=x | | 2x+18+5x-3x=90 | | 3(y-2)+6y=12 | | Y=150(2) | | x/3-10=9 | | 5u+18=8u | | -3/v=3 | | .12x=17000 | | 5b-9b=16 | | 8x+48=16 | | 37=15x-5x-3 | | 5u=14+3u | | n/24=5/8 | | -7=-5w+2(w-8) | | 3x+6(x+2)=12 | | (3m-2)(3m-2)=0 | | 11y=7y+20 |